Social seducement: towards the foundations for a pedagogical model - Padilla Zea, Natalia; Aceto, Stefania; Burgos, Daniel (Ingeniería Solidaria, 2017)
Introduction: Social Seducement is a project intended to ease the re-entry of long-term unemployed people into society by involving them in the development of a social economy enterprise. This goal will be reached by giving them the opportunity to develop necessary skills via a serious game, in which they will learn the primary concepts, skills and attitudes for developing an enterprise successfully. This article was written in the year 2016 in the Universidad Internacional Methodology: This paper focuses on the process necessary to develop a pedagogical model for this game and on explaining the foundations to be observed, i.e., the instructional model, the way the approach is related to the European Qualifications Framework and the specific competencies that a social entrepreneur must develop. Results: As a result of this study, we obtained a didactical basis on which to support the process of game-based learning. Conclusions: Our immediate focus is the development of each phase of the addie (Analysis, Design, Development, Implementation, and Evaluation) model, developing external and internal material, placing content within the proper levels and testing the game in order to perform the piloting.